2022
DOI: 10.1021/acs.jpclett.2c01851
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Transport Orbitals in Single-Molecule Junctions

Abstract: Controlling charge transport through molecules is challenging because it requires engineering of the energy of molecular orbitals involved in the transport process. While side groups are central to maintaining solubility in many molecular materials, their role in modulating charge transport through single-molecule junctions has received less attention. Here, using two break-junction techniques and computational modeling, we investigate systematically the effect of electron-donating and -withdrawing side groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
5
22
1
Order By: Relevance
“…where Conductance Histograms. To construct conductance histograms shown in Figure S11, we follow the same procedure as in ref 26. First, we form a series of junctions with different contacting modalities to electrodes and calculate the electrical conductance G for a range of electrodes Fermi energies E F .…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where Conductance Histograms. To construct conductance histograms shown in Figure S11, we follow the same procedure as in ref 26. First, we form a series of junctions with different contacting modalities to electrodes and calculate the electrical conductance G for a range of electrodes Fermi energies E F .…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…25 Thiol anchors were chosen because they have high binding energy to electrodes (E B = 2.1 eV) and make good contacts to gold electrodes experimentally. 26 To demonstrate that spin interference can be different in these radicals compared to their closed-shell counterparts, we also studied a closed-shell analogue of TPM-B where the boron atom was replaced with a carbon atom (TPM in Figure 1b).…”
mentioning
confidence: 99%
“…Porphyrins, which stand for a sort of natural tetrapyrrolic macrocycle system, provide a good starting point for building molecular devices and have been studied extensively as molecular devices in the form of the complex monomer, oligomer, fused structures and through-space π–π stacked structures . However, to our knowledge, despite fascinating features such as low conductance attenuation at long molecular length, , the tunable conductance by the image-charge effect and the central-coordinated metal, the systematic investigation on the influence of substituents, which is a primary effect in regulating energy level of molecular junctions and further the single-molecule conductance, on the side groups of the conductive backbones in tetrapyrrolic macrocycles, has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We then employed (Figures S13−S16) DFT combined with the nonequilibrium Green's function (NEGF) method to optimize and calculate the transmission probability of these two supramolecular co-conformations and plot (Figure 1g) the calculated transmissions versus energy. 55 We found that the electron transmission probability of the [π•••π] stacked dimer junctions with parallelly displaced co-conformations is approximately over 2 orders of magnitude larger than those with fully stretched hydrogen-bonded co-conformations. In addition, [π•••π] stacked and hydrogen-bonded dimers exhibit (Figures S17−S19) different quantum interference effects primarily on account of the alternations 56 in the phase of orbitals.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…In energy terms (Figure S10), the [π···π] stacked dimer (Figure e) is more favorable, while the hydrogen-bonded co-conformation (Figure f) represents a metastable state which, although it is 5.0–6.0 kcal/mol higher in energy, can be attained by the nanoscale motion of the electrodes. We then employed (Figures S13–S16) DFT combined with the nonequilibrium Green’s function (NEGF) method to optimize and calculate the transmission probability of these two supramolecular co-conformations and plot (Figure g) the calculated transmissions versus energy . We found that the electron transmission probability of the [π···π] stacked dimer junctions with parallelly displaced co-conformations is approximately over 2 orders of magnitude larger than those with fully stretched hydrogen-bonded co-conformations.…”
Section: Results and Discussionmentioning
confidence: 99%